Pengembangan Instrumen Penilaian Portofolio (Studi Kasus Pada Mata Pelajaran Teknologi Informasi dan Komunikasi (TIK) Kelas VII Bahasan Perangkat Keras, Perangkat Lunak, dan Kegunaan Program Aplikasi, Siswa SMP Negeri 1 Selat Karangasem) - Agung Istri Ariningrat, I Gusti; Eka Damayanthi, Luh Putu; Windu Antara Kesiman, Made; Gede Sunarya, I Made (Universitas Pendidikan Ganesha, 2014)
The aim of this study was to produce a valid, reliable, and practical portfolio assessment instrument to assess students ability, particularly to the development of assessment instruments portfolio discussion of hardware, software, and usefulness of the application program. The validation process of the portfolio assessment instrument was conducted in two stages, namely through the theoretical validation and empirical validation.Validation of theoretical validation is determined by expert judgment or assessment, while the empirical validation is determined by the validity of the specific criteria for testing to student in order to measure the ability of students. For content validity rate was calculated using the Gregory formula, and the value obtained classified in either category. Second step validation, was the data of empirical test results. This data then, was used to find the validity and reliability of the developed instrument. The instrument validity was calculated using the formula correlation product momment, the results obtained that 4 items were invalid, Item numbers 2, 8, 9, and 12, while for the instrument reliability was calculated using Cronbach alpha formula which had moderate reliability value. For interater reliability involved two (2) teachers as assessors. From the data obtained, then it was calculated using the Ebel formula and had a value that was a very high degree of reliability. Furthermore, the practicality of the instrument was calculated using the theoretical ideal benchmark assessment, and had a very practical level criteria